Cell response to substrate rigidity is regulated by active and passive cytoskeletal stress - Doss, Bryant L.; Pan, Meng; Gupta, Mukund; Grenci, Gianluca; Mège, René Marc; Lim, Chwee Teck; Sheetz, Michael P.; Voituriez, Raphaël; Ladoux, Benoît (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Morphogenesis, tumor formation, and wound healing are regulated by tissue rigidity. Focal adhesion behavior is locally regulated by stiffness; however, how cells globally adapt, detect, and respond to rigidity remains unknown. Here, we studied the interplay between the rheological properties of the cytoskeleton and matrix rigidity. We seeded fibroblasts onto flexible microfabricated pillar arrays with varying stiffness and simultaneously measured the cytoskeleton organization, traction forces, and cell-rigidity responses at both the adhesion and cell scale. Cells adopted a rigidity-dependent phenotype whereby the actin cytoskeleton polarized on stiff substrates but not on soft. We further showed a crucial role of active and passive cross-linkers in rigidity-sensing responses. By reducing myosin II activity or knocking down α-actinin, we found that both promoted cell polarization on soft substrates, whereas α-actinin overexpression prevented polarization on stiff substrates. Atomic force microscopy indentation experiments showed that this polarization response correlated with cell stiffness, whereby cell stiffness decreased when active or passive cross-linking was reduced and softer cells polarized on softer matrices. Theoretical modeling of the actin network as an active gel suggests that adaptation to matrix rigidity is controlled by internal mechanical properties of the cytoskeleton and puts forward a universal scaling between nematic order of the actin cytoskeleton and the substrate-to-cell elastic modulus ratio. Altogether, our study demonstrates the implication of cell-scale mechanosensing through the internal stress within the actomyosin cytoskeleton and its coupling with local rigidity sensing at focal adhesions in the regulation of cell shape changes and polarity.
CRIS-Team Scopus Importer:2024-02-19
Keywords: Cell polarity; Cytoskeleton; Mechanobiology; Rigidity sensing